Prediction of potential suitable habitats in the 21st century and GAP analysis of priority conservation areas of Chionanthus retusus based on the MaxEnt and Marxan models - Wang, Yongji; Wu, Kefan; Zhao, Ruxia; Xie, Liyuan; Li, Yifan; Zhao, Guanghua; Zhang, Fen-Guo (Frontiers in Plant Science, 2024)
Chionanthus retusus(C. retusus) has a high economic and medicinal value, but in recent years it has been included in the list of China's major protected plants and China's Red List of Biodiversity due to the serious destruction of its wild germplasm resources. In this paper, based on 131 sample points of the natural distribution of C. retusus applied Maxent model after optimisation using the ENMeval package, combined with the geographic information system ArcGIS to simulate the 21st century potential habitat of the C. retusus and its spatial changes, prioritizing protected areas using the Marxan model and using GAP analysis to assess current conservation status. The results showed that (1) when the regularization multiplier was 1.5 and the feature combinations were linear, quadratic, and fragmented, the area under the curve of the subjects in the training and test sets were 0.960 and 0.941, respectively, which were both above 0.9, the true skill statistic value was 0.80, and the maximum Kappa value was 0.62, meaning that the model had high accuracy; (2) Climate, soil, and topographic factors combine to influence the potential geographic distribution of C. retusus, with temperature seasonality, annual precipitation, min temperature for coldest month and precipitation of wettest month accounted for a relatively large influence. (3) The moderately and optimally suitable habitats of C. retusus are primly located in the areas of southwestern Shanxi, central Hebei, western Henan, Shandong, Shaanxi, Anhui and Hubei through simulation; (4) Under different future climate scenarios, the area of each class of suitable habitat increases by varying amounts compared to the current period, with a general trend of expansion to the south; (5) The C. retusus priority protected areas are mainly located in most of Shandong, southern Liaoning, southwestern Shanxi, western Henan, and central Hebei, and its conservation vacancy area is relatively large compared to its protected area. These results will provide scientific strategies for implementing long-term conservation of C. retusus in China and similar regions under warming conditions in the 21st century.